Nexus between financial development and energy poverty in Latin America - Mohsin, Muhammad; Taghizadeh-Hesary, Farhad; Shahbaz, Muhammad (Energy policy, 2022)
This paper estimates the association of financial development with energy poverty in Latin America through the entropy method, the Principal Component Analysis (PCA), and an econometric analysis. Energy poverty scores of Latin American countries are less than unitary, making up for 17.54 percent, which implies that 17.45 percent of the residents did not attain the efficiency frontier of adequate energy consumption. Within all quantiles, the results elucidate that increases in energy poverty are attributed to low levels of financial development. The study provides policy recommendations for energy poverty alleviation through financial development. •We analysed the association of multidimensional energy poverty and financial advancement in the Latin American region.•Financial development and FDI as the key variables in alleviating energy poverty.•Energy poverty scores of Latin American countries are less than unitary.•17.45 percent of the residents did not attain the efficiency frontier of adequate energy consumption.•Increases in energy poverty are attributed to low levels of financial development.